High Ghrelin Levels in Post-treatment Euthyroid Patients with Hashimoto’s Thyroiditis: a Case-control Preliminary Study - Malandrino, N.; Miceli, A.; Leggio, L.; Mingrone, G.; Capristo, E. (Experimental and Clinical Endocrinology & Diabetes, 2014)
Rationale: Hashimoto’s thyroiditis is a chronic inflammatory condition often associated with changes in appetite and body composition. Ghrelin is an orexigenic peptide involved in the regulation of appetite and food intake. A possible role of ghrelin in mediating inflammation has been suggested. A few contrasting published data are available on the relationship between thyroid status and circulating ghrelin in patients affected by Hashimoto’s thyroiditis. The aim of the present case-control study was to provide additional evidence on the relationship between thyroid status and plasma ghrelin levels in post-treatment euthyroid female patients with Hashimoto’s thyroiditis, compared to healthy controls.Methods: 25 women [age 46.6±10.6 years; Body Mass Index 26.3±3.8 kg/m²] affected by overt hypothyroidism due to Hashimoto’s thyroiditis were studied after thyroid hormones and body weight were already normalized for at least 2 months following L-thyroxine replacement. 25 healthy women (age 40.2±6.4 years; Body Mass Index 26.2±4.0 kg/m²) served as the control group. Blood levels of thyroid hormones, thyroid peroxidase antibodies, thyroglobulin antibodies and ghrelin were determined. Fat mass, fat-free mass and high-density lipoprotein cholesterol were also assessed.Results: Circulating ghrelin levels were significantly higher in patients vs. control subjects (p<0.001). No differences were found in metabolic parameters (body mass index, fat mass, fat-free mass, high-density lipoprotein cholesterol) between groups.Conclusion: The present study provides additional evidence of hyperghrelinemia status in post-treatment euthyroid patients affected by Hashimoto’s thyroiditis.
Keywords: ghrelin; thyroid hormones; Hashimoto’s thyroiditis; inflammation; metabolism